2015
DOI: 10.1016/j.mayocp.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Forward in Cardiovascular Disease Prevention One and a Half Years After Publication of the 2013 ACC/AHA Cardiovascular Disease Prevention Guidelines

Abstract: The 2013 American College of Cardiology / American Heart Association (ACC/AHA) prevention guidelines represent an important step forward in both the risk assessment and management of atherosclerotic cardiovascular disease in clinical practice. Differentiated risk prediction equations for women and African Americans were developed, and convenient 10-year and lifetime risk assessment tools were provided, facilitating their implementation. Lifestyle modification was portrayed as the foundation of preventive thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…These risk prediction tools may provide accurate estimates of long-term risk [23], but the PCE particularly has been shown to overestimate CVD risk in general populations [33, 34]. In contrast, our findings support another recent study that reported that the FRS and PCE underestimate CVD risk in HIV-infected populations [35].…”
Section: Discussionsupporting
confidence: 82%
“…These risk prediction tools may provide accurate estimates of long-term risk [23], but the PCE particularly has been shown to overestimate CVD risk in general populations [33, 34]. In contrast, our findings support another recent study that reported that the FRS and PCE underestimate CVD risk in HIV-infected populations [35].…”
Section: Discussionsupporting
confidence: 82%
“…43 The MESA study played a prominent role in describing how so-called “negative risk factors” can be used to down-classify risk in certain situations. 36,44-46 In a study of 13 negative risk factors, Blaha et al used risk factor-adjusted diagnostic likelihood ratios (DLRs) to demonstrate that a CAC score of zero was the strongest negative risk factor (0.41), followed by a normal carotid ultrasound (0.65) and a negative family history of CHD (0.76) (Figure 4).…”
Section: Mesa and The Clinician-patient Risk Discussionmentioning
confidence: 99%
“…These treatment goals are based on the present evidence for reducing morbidity and mortality connected to different medical conditions. The goals have been sharpened in recent years, and experts recommend more aggressive treatment with statins [26], although full agreement has not been achieved [27]. Compared with primary prevention, statin therapy is more important in secondary prevention, e.g.…”
Section: General Practicementioning
confidence: 99%